INTEGRASI DATA BARANG PADA SISTEM INVENTORY CV. XYZ MENGGUNAKAN WEB SERVICE - Trianggara, Dhani; Witanti, Wina; Ashaury, Herdi (Jurnal Informatika, 2022)
In various fields the industry has used as well as implemented the concept of web services that provide message interoperability and data exchange interfaces. One of the uses for sharing data on data integration of one system with another system in this case study was carried out to manage iron supply goods data, in CV. XYZ Pratama Manufacture Engineering uses research methods of collecting data structures, architectural design data, building application web services, building Rest APIs, testing, and measuring and securing JWT HS 256 tokens. Building integration can formulate how to use CV Goods data. XYZ, becomes an Inventory system built using Web Service technology by managing item API data of json data type on the Rest Server so that it can be used by Client Rest. This research resulted in a Web Service through testing stages with different services with the total data requested and received which is 62.48 kb and the total Response time from data retrieval 2.2 seconds with an average execution time of Request data of 177 milli seconds.